OVERCROWDING WARGA BINAAN DI LEMBAGA PEMASYARAKATAN DITELISIK DARI PERSPEKTIF VIKTIMOLOGI (STUDI TERHADAP OVERCROWDING WARGA BINAAN DI PROVINSI RIAU) - Munir, Abdul; Prihatin, Panca Setyo; Freddy, Harapan Tua Ricky; Saudi, Ahmad (JURNAL TRIAS POLITIKA, 2024)
Abstract: Overcrowding in Prisons and Detention Centers in Indonesia is not a new phenomenon. Data shows that overcrowding has persisted and even tended to increase over the last decade. This situation has adverse effects on inmates and prisoners serving their sentences, such as health issues and the effectiveness of punishment. This study aims to conduct an in-depth analysis of the overcrowding phenomenon among inmates in Prisons/Detention Centers. The rationale for this study is that overcrowding can hinder the achievement of the primary goal of the Correctional Institution, which is to rehabilitate inmates so they can reintegrate into society as reformed individuals. Using a qualitative approach, this research employs a literature review technique, relying on secondary data drawn from books, journals, documents, and online news sources related to the research theme. The analysis is conducted using three inclusion criteria to answer the research questions. By applying the critical theory of new victimology, this study presents a new discourse on structural victims resulting from the suboptimal functioning of the legal system. The findings indicate that overcrowding is caused by weak coordination among law enforcement agencies, leading to humanitarian issues and structural victimization due to the neglect of overcrowding in Prisons and Detention Centers. Abstrak: Overcrowding pada Lapas dan Rutan di Indonesia bukanlah fenomena baru. Data menunjukkan setidaknya dalam 10 tahun terakhir overcrowding masih terus terjadi dan cenderung meningkat. Hal ini membawa dampak lain terhadap warga binaan dan narapidana yang menjalani masa hukumannya seperti masalah kesehatan dan efektifitas hukuman. Penelitian ini bertujuan menganalisis secara mendalam tentang fenomena overcrowding warga binaan di Lapas/Rutan. Alasan dari kajian ini bahwa fenomena overcrowding dapat menghambat capaian atau tujuan akhir dari fungsi Lembaga Pemasyarakatan sebagai wadah pembinaan bagi warga binaan untuk dapat kembali ditengah masyarakat sebagai orang yang baik. Dengan pendekatan kualitatif, penelitian ini menggunakan teknik studi literatur mengandalkan data sekunder yang diambil dari buku, jurnal, dokumen dan sumber berita online yang terkait dengan tema penelitian yang dianalisis melalui tiga kriteria inklusi untuk menjawab pertanyaan penelitian. Dengan menggunakan teori kritis new viktimologi, sebuah wacana baru tentang korban struktural akibat kurang berjalannya sistem penyelenggaraan hukum secara optimal. Ditemukan overcrowding disebabkan lemahnya koordinasi lembaga penegak hukum yang mengakibatkan masalah kemanusian serta viktimisasi struktural atas pembiaran overcrowding di Lapas dan Rutan.